High‐Energy‐Density Supercapacitors Based on Patronite/Single‐Walled Carbon Nanotubes/Reduced Graphene Oxide Hybrids. Issue 2 (9th December 2015) - Ratha, Satyajit; Marri, Subba R.; Behera, J. N.; Rout, Chandra Sekhar
Abstract: The facile hydrothermal synthesis of a patronite VS4 /single‐walled carbon nanotube/reduced graphene oxide hybrid is reported. Detailed electrochemical investigations of the hybrid revealed an exceptionally high energy density of ca. 174 W h/kg. A comparison of this value with those of other supercapacitor electrodes based on metal sulfides and also some with high energy‐density values revealed the potential of the patronite hybrid as a fitting candidate for possible application in energy‐storage devices. Charge–discharge stability measurements showed the excellent specific capacitance of the hybrid, which has a retention capability of ca. 97 % after 1000 continuous charge–discharge cycles. Abstract : High‐energy‐density supercapacitors based on VS4 /carbon nanotubes/reduced graphene oxide (VS4 /CNTs/RGO) hybrids are synthesized for possible application as energy‐storage devices.